Neural Circuits for Social Interactions: From Microcircuits to Input-Output Circuits - Xu, Sen; Jiang, Ming; Liu, Xia; Sun, Yahan; Yang, Liang; Yang, Qinghu; Bai, Zhantao (Frontiers in Neural Circuits, 2021)
Social behaviors entail responses to social information and requires the perception and integration of social cues through a complex cognition process that involves attention, memory, motivation, and emotion. Neurobiological and molecular mechanisms underlying social behavior are highly conserved across species, and inter- and intra-specific variability observed in social behavior can be explained to large extent by differential activity of a conserved neural network. However, neural microcircuits and precise networks involved in social behavior remain mysterious. In this review, we summarize the microcircuits and input-output circuits on the molecular, cellular, and network levels of different social interactions, such as social exploration, social hierarchy, social memory, and social preference. This review provides a broad view of how multiple microcircuits and input-output circuits converge on the medial prefrontal cortex, hippocampus, and amygdala to regulate complex social behaviors, as well as a potential novel view for better control over pathological development.